Evaluation of electrocardiography after combined use of ondansetron and diltiazem in anesthetized rats [Diltiazemin ondansetron ile birlikte kullanımının anestezi almış sıçan elektrokardiyografisi üzerindeki etkisinin deǧerlendirilmesi] - (:unkn) unknown (Turkiye Klinikleri, 2013)
Objective: This study investigated the changes in electrocardiograms in rats after combined use of ondansetron and diltiazem. Material and Methods: Seventeen rats were included in the study but data were collected from 11 rats with available data. After anesthesia, electrocardiogram records of rats for the initial 5 minutes were considered "Baseline" record. Following this, rats received intravenous ondansetron injection and their electrocardiograms were recorded for another 5 minutes. The same procedure was repeated with intravenous diltiazem injection. Results: After ondansetron injection QTc from 9 rats were longer and 2 rats were shorter compared to baseline (before the administration of ondansetron). When diltiazem was given after ondansetron, in 10 rats out of 11, the QTc time was correlated negatively with measurements obtained before diltiazem. There was no statistically significant difference between the baseline QTc measurements and the QTc obtained after the administration of diltiazem. Conclusion: The combined use of ondansetron and diltiazem does not lead to any change in rat electrocardiography. © 2013 by Türkiye Klinikleri.
Keywords: Diltiazem; Electrocardiography; Ondansetron